Mesa de negociação permanente do SUS implantada em um município do Espírito Santo : espaço de negociação do trabalho? - Santos, Elisangela Coco dos (2015)
The legitimate space, used in the labor negotiation process between managers and workers of SUS, is the Permanent Negotiation Roundtable of the Trading Unified Health System (SUS-MNP). The aim of this study is to analyze the process of collective bargaining between the components of the Municipal Negotiation Roundtable of SUS established in 2007 in Vitória-ES. This research is qualitative exploratory held in two stages: a) literature: with the use of descriptors productive: restructuring, collective bargaining on health system and permanent negotiation roundtable on health system. b) documentary research: internal regulament of roundtable, municipal laws, municipal ordinances and meeting minutes available on Vitória‟s Council hot site. The study‟s data collection comprised the years 2007 to 2013 and the content of 53 meeting minutes available were analyzed. The Vitória‟s Negotiation Roundtable consists of 12 managers of the Health and Administration Secretariats‟ and 12 health workers' unions representatives. The results shows an expressive representation of managers. Between workers' representatives was relevant the presence of SINODONTO and SISMUV. The most important agenda points were related to Improvement Program Access of Quality, implemented by the municipality, and The Functional Evolution of the Civil Servant and Salary Bonus. We recognize the importance of strengthening the collective negotiation space at SUS in order to ensure continuity and civil servants‟ approximation in the public service.